The Influence of Celebrity Endorser, Brand Image, and EWOM on Consumer Purchase Decisions of Sunco Cooking Oil : Pengaruh Celebrity Endorser, Citra Merek Dan E-Wom Terhadap Keputusan Pembelian Konsumen Pada Minyak Goreng Sunco - Atika Dwi Wardani; Lilik Indayani (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to determine celebrity endorsers, brand image, and E-WOM on consumer purchasing decisions on Sunco cooking oil (study in Sedati Gede Village, Sidoarjo Regency). This research is a descriptive study using quantitative methods. The data collection technique is by distributing questionnaires to 100 respondents who are customers of Sunco cooking oil. The analysis technique used in this study is multiple linear regression using the SPSS (Statistical Program for Social Science) version 18 for windows. The results of this study indicate that the celebrity endorser variable has an effect on purchasing decisions, the brand image variable has an effect on purchasing decisions, and E-WOM has an effect on purchasing decisions for consumers of Sunco cooking oil (study in Sedati Gede Village, Sidoarjo Regency).